Chromosomal aberrations and fusion genes in myeloid malignancies. Issue 4 (August 2012) - Gianfelici, Valentina; Lahortiga, Idoya; Cools, Jan
Since the discovery of the BCR–ABL1 fusion gene in chronic myeloid leukemia, many more fusion genes resulting from chromosomal rearrangements have been identified and characterized. The study of these fusion genes has been extremely important for our understanding of the role of chromosomal rearrangements in leukemogenesis and in oncology in general. In chronic myeloid leukemia, or related myeloproliferative malignancies caused by the expression of oncogenic fusion kinases, tyrosine kinase inhibitors are now successfully used to treat these diseases. In acute myeloid leukemias, the presence of chromosomal rearrangements, oncogenic fusion genes and point mutations in key oncogenic drivers has important prognostic value and determines the choice of therapy. In this review, the authors provide an overview of the important fusion genes present in various myeloid malignancies and their importance for clinical practice.